Thermoanalytical curves for Yamato-74013 and -74010 diogenites - Lang,Bruno; Grodzinski,Andrzej; Stoch,Leszek (1983)
P(論文) Within a thermoanalytical study of a number of meteorites were obtained differential thermal (DTA) and thermogravimetric (TG) curves for the Yamato-74013 and -74010 diogenites. Small lithic fragments (blebs) and fines were taken for samples, occasionally weathered. Heating both in air and oxidation-suppressing in Ar was applied up to 1200℃, but the interval not exceeding 700℃ appeared relevant for analysis. The thermoanalytical data were tabulated. The major features on the DTA-curves were found to originate from oxidation of troilite to pyrrhotite and magnetite, being followed by further partial oxidation of magnetite to maghemite and hematite. The consistence was shown of the thermoanalytical and thermomagnetic data, while possible interference of thermal effects with magnetic properties of minerals hypothesized. The similarity of the thermoanalytical curves for both diogenites examined suggests the support to the view that they came from a single fall. departmental bulletin paper